Recommendations for performing, interpreting and reporting hydrogen deuterium exchange mass spectrometry (HDX-MS) experiments - Masson, Glenn R; Burke, John E; Ahn, Natalie G; Anand, Ganesh S; Borchers, Christoph; Brier, Sébastien; Bou-Assaf, George M; Engen, John R; Englander, S Walter; Faber, Johan; Garlish, Rachel; Griffin, Patrick R; et al. (Nature methods, 2019)
Hydrogen deuterium exchange mass spectrometry (HDX-MS) is a powerful biophysical technique being increasingly applied to a wide variety of problems. As the HDX-MS community continues to grow, adoption of best practices in data collection, analysis, presentation and interpretation will greatly enhance the accessibility of this technique to nonspecialists. Here we provide recommendations arising from community discussions emerging out of the first International Conference on Hydrogen-Exchange Mass Spectrometry (IC-HDX; 2017). It is meant to represent both a consensus viewpoint and an opportunity to stimulate further additions and refinements as the field advances.
Keywords: koncentrace vodíkových iontů; analýza dat; hmotnostní spektrometrie; Deuterium Exchange Measurement; Hydrogen-Ion Concentration; Data Analysis; Mass Spectrometry; vodík-deuteriová výměna